Zirconium and hafnium fractionation and distribution of Rare Earth Elements in neutral-alkaline waters: Case study of Lake Van hydrothermal system, Turkey - Sasmaz, A.; Zuddas, P.; Cangemi, M.; Piazzese, D.; Ozek, G.; Venturi, M.; Censi, P. (Elsevier, 2021)
We investigated the distribution of Zr, Hf, and rare earth elements (REE) as the sum of lanthanides plus Y in the hydrothermal system in the Lake Van area of south-eastern Turkey. This system is characterised by water with variable pH in alkaline conditions resulting from hydrothermal CO2 upraise and neoformation of calcite minerals in near equilibrium with the interacting waters. Zr, Hf, and REE determinations were carried out for aqueous phases and suspended solids in lake water and surrounding thermal springs. We found that dissolved Hf is partitioned relative to Zr during calcite formation and that such fractionation is a function of the Ca2+ activity in warm water. The observed Zr-Hf fractionation is explained by coulombic interactions that occur between suspended solid particles and dissolved phases at the calcite-water interface. There, the surfaces of carbonate minerals demonstrated greater reactivity towards aqueous Hf-bearing species relative to Zr-complexes. This evidence involves a coulombic mechanism of reactivity at the calcite-water interface because Hf complexes are negatively charged while Zr compounds are uncharged. Thus, authigenic calcite can behave as a suitable host for dissolved metal ion species to adsorb on crystal surfaces to remediate waste waters from mine drainage.
Keywords: Zr; Hf ratio; REE; Alkaline lakes; Turkey